Decline in CD4 T lymphocytes with monotherapy bridging strategy for non-adherent adolescents living with HIV infection: Results of the IMPAACT P1094 randomized trial - Allison L. Agwu (2018)
Introduction: Management of persistently non-adherent youth living with HIV (YLHIV) with virologic failure (VF) on combination antiretroviral therapy (cART) remains challenging. One strategy has been using 3TC/FTC monotherapy (3TC/FTC), which in the presence of the M184V resistance mutation, does not suppress viral replication nor select for additional drug resistance mutations, and reduces viral fitness with limited side effects. P1094 compared the immunologic outcome of continuing failing cART vs. switching to 3TC/FTC as a "bridging strategy" to subsequent suppressive cART for non-adherent YLHIV with pre-existing M184V resistance. Materials & methods: Participants with documented nonadherence, M184V mutation, CD4 + T cell count ≥100 cells/mm 3 and VF (HIV-1 plasma RNA ≥400 copies/mL (2.6 log 10 HIV-1 RNA) were enrolled and randomized to continue failing cART vs. switch to 3TC/FTC. The primary endpoint (time to ≥30% CD4 + T cell decline or development of CDC class C events) at 28-weeks were assessed by Kaplan-Meier (K-M) curves in an intent-to-treat analysis. Results: Thirty-three perinatally acquired YLHIV participants (16 continuing cART and 17 3TC/FTC) enrolled in the study. The median age, entry CD4 + T cell count, and viral load were 15 years (Inter-quartile range (IQR) 14-20), 472 cells/mm 3 (IQR 384-651), and 4.0 log 10 HIV-1 RNA copies/ml (IQR 3.2-4.5), respectively. Five participants, all in the 3TC/FTC arm, reached the primary endpoint for absolute CD4 + T cell decline (p = 0.02, exact log-rank test comparing monotherapy to cART). The Kaplan-Meier estimate of probability of primary endpoint on 3TC/FTC at 28 weeks was 0.41 (standard error 0.14). There were no CDC class C events or deaths and no statistically significant difference in frequencies of adverse events between the arms. Conclusions: Non-adherent participants randomized to 3TC/FTC were more likely than those maintained on failing cART to experience a confirmed decline in CD4 + count of ≥30%. Although this study suffers from limitations of small sample size and premature discontinuation, the randomized comparison to continuing failing cART indicates that 3TC/FTC provides inferior protection from immunologic deterioration for non-adherent youth with M184V resistance. Better alternatives to 3TC/FTC such as ART with higher barriers to resistance and novel adherence and treatment strategies for nonadherent youth are urgently needed. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.